2023
DOI: 10.1002/csc2.20969
|View full text |Cite
|
Sign up to set email alerts
|

Early generation seed starter materials and approaches to seed production: Challenge for improving the potato seed system in Uganda

Abstract: Quality seed is one of the key inputs for increasing potato (Solanum tuberosum L.) productivity; however, its limited availability is widely recognized as a major constraint to potato production. In Uganda, certified seed production meets approximately 1.5% of effective demand implying most farmers use home‐saved seed. This practice encourages the buildup of degenerative seed‐borne diseases which ultimately affect productivity. Consequently, a study was conducted to determine the productivity of different seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The authors showed promising results in terms of cost reduction compared to conventional minitubers and concluded that the current challenge is to build demand for this approach and educate downstream multipliers on the technique. In Uganda, results from Namugga et al (2024) indicated that for the two potato varieties studied, plants whose origin was tissue culture raised plantlets were more productive in terms of the number of tubers produced than when the source was apical cuttings, but average weight per tuber produced was higher from the apical cutting source.…”
Section: Crop Sciencementioning
confidence: 99%
“…The authors showed promising results in terms of cost reduction compared to conventional minitubers and concluded that the current challenge is to build demand for this approach and educate downstream multipliers on the technique. In Uganda, results from Namugga et al (2024) indicated that for the two potato varieties studied, plants whose origin was tissue culture raised plantlets were more productive in terms of the number of tubers produced than when the source was apical cuttings, but average weight per tuber produced was higher from the apical cutting source.…”
Section: Crop Sciencementioning
confidence: 99%
“…As a vegetative reproductive organ, part of its physiological development in the plant and post-harvest, the tuber goes through a state of rest or dormancy, a period of relative inactivity before sprout formation. The latency period is characteristic of each variety, and its duration is crucial for planting [18]. This period ends with the initiation of the first sprout's growth.…”
Section: Sprouting Of the Seed Tuber And Sprout Growthmentioning
confidence: 99%